The Use of Various Concentrations of EM4 (Effective Microorganism-4) with Moringa Leaves (Moringa oleifera) as Animal Feed to Reduce Ammonia Levels in Broiler Chicken Manure and Its Implementation in Environmental Pollution Materials - Andi Badli Rompegading; Darwis; Rizal Irfandi (Postgraduate, University of Mataram, 2025)
This study was motivated by the pungent odor of broiler manure around the farm. Chicken manure that accumulates in chicken coops and accumulates in large quantities will produce harmful gases such as ammonia. Therefore, an alternative solution is needed to manage chicken manure so that the ammonia content is not high. One process that can be used is to provide EM4 and Moringa leaves as animal feed. The purpose of this study was to determine the concentration of EM4 and Moringa leaves that can stabilize ammonia levels in broiler manure. This research is an experimental study using a group randomized design consisting of 4 treatments and each treatment used 1 kg of animal feed and each was given 2 replicates for 4 weeks. With data analysis techniques using the Anova test and the Honest Real Difference test. The design is as follows: A0: 1 kg of animal feed without EM4 and moringa leaves, A1: 1 kg of animal feed with 15 ml EM4 and 9 gr moringa leaves, A2: 1 kg of animal feed with 25 ml EM4 and 9 gr moringa leaves, A3: 1 kg of animal feed with 35 ml EM4 and 9 g moringa leaves. The results of the research conducted obtained that the concentration of EM4 with moringa leaves as the right animal feed is 25 ml EM4 and 9 gr moringa leaves (A2) where the result is the ammonia level of 10 ppm.